Representasi Visual Kesehatan Mental Pada Serial Film Televisi Parasyte: The Grey (Analisis Semiotika Charles Sanders Peirce) - Fitra Nurary Arasyid Herliyan Putra (CV Edujavare Publishing, 2024)
This study examines the visual representation of mental health in the television series